"Interactive Methods of Teaching English Language in Primary School" (Eurasian Research Bulletin, 2022)
The article discusses interactive methods of teaching English. The possibility of using some of these methods and techniques in English classes is described. The interactive teaching method increases motivation in learning English, the learning process becomes more interesting and entertaining, and pupils feel freer.